Targeted Delivery of Epidermal Growth Factor to the Human Placenta to Treat Fetal Growth Restriction - Lewis J. Renshall; Frances Beards; Angelos Evangelinos; Susan L. Greenwood; Paul Brownbill; Adam Stevens; Colin P. Sibley; John D. Aplin; Edward D. Johnstone; Tambet Teesalu; Lynda K. Harris (MDPI AG, 2021)
Placental dysfunction is the underlying cause of pregnancy complications such as fetal growth restriction (FGR) and pre-eclampsia. No therapies are available to treat a poorly functioning placenta, primarily due to the risks of adverse side effects in both the mother and the fetus resulting from systemic drug delivery. The use of targeted liposomes to selectively deliver payloads to the placenta has the potential to overcome these issues. In this study, we assessed the safety and efficacy of epidermal growth factor (EGF)-loaded, peptide-decorated liposomes to improve different aspects of placental function, using tissue from healthy control pregnancies at term, and pregnancies complicated by FGR. Phage screening identified a peptide sequence, CGPSARAPC (GPS), which selectively homed to mouse placentas in vivo, and bound to the outer syncytiotrophoblast layer of human placental explants ex vivo. GPS-decorated liposomes were prepared containing PBS or EGF (50-100 ng/mL), and placental explants were cultured with liposomes for up to 48 h. Undecorated and GPS-decorated liposomes containing PBS did not affect the basal rate of amino acid transport, human chorionic gonadotropin (hCG) release or cell turnover in placental explants from healthy controls. GPS-decorated liposomes containing EGF significantly increased amino acid transporter activity in healthy control explants, but not in placental explants from women with FGR. hCG secretion and cell turnover were unaffected by EGF delivery; however, differential activation of downstream protein kinases was observed when EGF was delivered via GPS-decorated vs. undecorated liposomes. These data indicate that targeted liposomes represent a safe and useful tool for the development of new therapies for placental dysfunction, recapitulating the effects of free EGF.